KUALITAS PRODUK, FAKTOR BUDAYA DAN KEPERCAYAAN (TRUST) TERHADAP PERILAKU KONSUMEN PADA PT. HWA LIEN STEEL FACTORY DI KABUPATEN TANGERANG - Siska Mayratih; Kusdianto Kusdianto; Isrok Isrok (Jurnal Comparative: Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of product quality, cultural factors and trust on consumer behavior at PT. Hwa Lien Steel Factory in Tangerang Regency. The sample in this study was 60 respondents at PT. Hwa Lien Steel Factory. The sampling technique used is probability sampling technique. Primary data collection was obtained from distributing questionnaires and secondary data obtained from companies. The analysis technique used is multiple linear regression analysis using SPSS version 26 software. The results of testing the hypothesis with the t test obtained empirical evidence that the product quality variable has a significant value of 10.773 > 2.003, the cultural factor variable has a significant value equal to the result value t count > t table i.e. 4.490 > 2.003, the trust variable has a significant value equal to the result value tcount > ttable, namely 3.088 > 2.003. It can be concluded that product quality, cultural factors and trust have a significant effect on customer behavior partially. The test results using the F test showed that product quality, cultural factors and trust in consumer behavior with a value of F = 79.152 with a probability significance level (0.000) <0.05. The coefficient of determination obtained is 0.799 . This means that 79.9% of variations in consumer behavior can be explained by variations of the four independent variables, namely product quality, cultural factors and trust. While the remaining 20.4% (100% - 79.9% = 20.1%) is explained by reasons other than the model.